Application of hypoxia-mesenchymal stem cells in treatment of anaerobic bacterial wound infection: wound healing and infection recovery - Andalib, Elahe; Kashfi, Mojtaba; Mahmoudvand, Golnaz; Rezaei, Elaheh; Mahjoor, Mohamad; Torki, Alireza; Afkhami, Hamed (Frontiers in Microbiology, 2023)
Mesenchymal stromal cells, commonly referred to as MSCs, are a type of multipotent stem cells that are typically extracted from adipose tissue and bone marrow. In the field of tissue engineering and regenerative medicine, MSCs and their exosomes have emerged as revolutionary tools.Researchers are now devoting greater attention to MSCs because of their ability to generate skin cells like fibroblasts and keratinocytes, as well as their distinctive potential to decrease inflammation and emit pro-angiogenic molecules at the site of wounds. More recent investigations revealed that MSCs can exert numerous direct and indirect antimicrobial effects that are immunologically mediated. Collectively, these antimicrobial properties can remove bacterial infections when the MSCs are delivered in a therapeutic setting. Regardless of the positive therapeutic potential of MSCs for a multitude of conditions, transplanted MSC cell retention continues to be a major challenge. Since MSCs are typically administered into naturally hypoxic tissues, understanding the impact of hypoxia on the functioning of MSCs is crucial. Hypoxia has been postulated to be among the factors determining the differentiation of MSCs, resulting in the production of inflammatory cytokines throughout the process of tissue regeneration and wound repair. This has opened new horizons in developing MSC-based systems as a potent therapeutic tool in oxygen-deprived regions, including anaerobic wound infection sites. This review sheds light on the role of hypoxia-MSCs in the treatment of anaerobic bacterial wound infection in terms of both their regenerative and antimicrobial activities.